How well do we understand pulsatility in the context of modern ventricular assist devices?. Issue 12 (December 2021) - Emmanuel, Sam; Jansz, Paul; Hayward, Christopher
Background: Modern ventricular assist devices (VADs) use a continuous flow design. It has been suggested that a lack of pulsatility contributes to a range of adverse outcomes including pump thrombus, gastrointestinal bleeding and stroke. To better assess the role of pulsatility in these adverse events, we first require a clear definition of 'pulsatility' in the setting of a severely impaired ventricle and a modern continuous flow VAD. Methods: A literature review was conducted to elucidate the understanding of pulsatility in modern VAD literature. Search engines used included PUBMED, EMBASE and the Cochrane library. Articles were appraised on three aspects: Whether they mentioned pulsatility; whether they mentioned which pulsatility measure was used and finally which methodology was used to obtain the value. Results: Of 354 articles reviewed, only 13 met our broad inclusion criteria. Of these articles, the most cited measure was pulsatility index (PI) – used by 11 of the publications. The methodology used to obtain the value was not uniform and five articles did not clearly state it. Other measures included pulse pressure and surplus haemodynamic energy. The majority of articles did not directly discuss pulsatility in the setting of patient-pump interaction. Conclusion: Most publications did not provide a definition for pulsatility. In those that did, the most common measure was PI. Measuring PI was not standardised. Few papers addressed the impact of intrinsic ventricular function and arterial compliance on pulsatility. We suggest that future publications adopt a uniform definition which encompasses both patient and pump characteristics.